Effects of propofol and its formulation components on macrophages and neutrophils in obese and lean animals - Luciana Boavista Barros Heil (Wiley, 2021)
Abstract We hypothesized whether propofol or active propofol component (2,6‐diisopropylphenol [DIPPH] and lipid excipient [LIP‐EXC]) separately may alter inflammatory mediators expressed by macrophages and neutrophils in lean and obese rats. Male Wistar rats (n = 10) were randomly assigned to receive a standard (lean) or obesity‐inducing diet (obese) for 12 weeks. Animals were euthanized, and alveolar macrophages and neutrophils from lean and obese animals were exposed to propofol (50 µM), active propofol component (50 µM, 2,6‐DIPPH), and lipid excipient (soybean oil, purified egg phospholipid, and glycerol) for 1 h. The primary outcome was IL‐6 expression after propofol and its components exposure by alveolar macrophages extracted from bronchoalveolar lavage fluid. The secondary outcomes were the production of mediators released by macrophages from adipose tissue, and neutrophils from lung and adipose tissues, and neutrophil migration. IL‐6 increased after the exposure to both propofol (median [interquartile range] 4.14[1.95–5.20]; p = .04) and its active component (2,6‐DIPPH) (4.09[1.67–5.91]; p = .04) in alveolar macrophages from obese animals. However, only 2,6‐DIPPH increased IL‐10 expression (7.59[6.28–12.95]; p = .001) in adipose tissue‐derived macrophages. Additionally, 2,6‐DIPPH increased C‐X‐C chemokine receptor 2 and 4 (CXCR2 and CXCR4, respectively) in lung (10.08[8.23–29.01]; p = .02; 1.55[1.49–3.43]; p = .02) and adipose tissues (8.78[4.15–11.57]; p = .03; 2.86[2.17–3.71]; p = .01), as well as improved lung‐derived neutrophil migration (28.00[−3.42 to 45.07]; p = .001). In obesity, the active component of propofol affected both the M1 and M2 markers as well as neutrophils in both alveolar and adipose tissue cells, suggesting that lipid excipient may hinder the effects of active propofol.